細胞懸濁液を安定吐出するための新規インクジェットヘッド - 打方, 佳郎; 増子, 龍也; 瀬尾, 学; 倉持, 譲; 松本, 貴彦; 高木, 大輔; 明石, 満; 中澤, 聡; 松崎, 典弥 (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
In vitro development of three-dimensional tissues is in high demand for regenerative medicine and drug screening. Here we present a novel inkjet head specialized for on-demand ejection of cell suspensions. Droplets are formed by membrane vibration, which is generated by a pulse actuation of the piezoelectric vibrator. During the non-ejecting period, the membrane is softly vibrated by a sinusoidal actuation to prevent the sedimentation of the cells inside the chamber.We performed an initial feasibility study by ejecting a suspension of normal human dermal fibroblasts (NHDF) using this inkjet head. By combining the ejecting actuation and the stirring actuation, the number of cells per droplets remained stable for more than thirty minutes and cell viability was over 90%.Next, we tried to construct three dimensional cardiac tissues by using cardiomyocytes derived from human iPS cells. Droplets with cardiomyocytes were ejected into the culture medium by repeating cycles of ejecting and stirring. After four days of incubation, the cells in the constructed cardiac tissue showed synchronous beating.These results indicate that this inkjet head is suitable for the effective ejection of living cells.